Citizenship in segmented societies lessons for the EU - edited by Francis Cheneval (Cheltenham Edward Elgar Publishing, 2018)
European Union citizenship is increasingly relevant in the context of both the refugee crisis and Brexit, yet the issue of citizenship is neither new nor unique to the EU. Using historical, political and sociological perspectives, the authors explore varied experiences of combining multiple identities into a single sense of citizenship.
Includes bibliographical references and index.
Keywords: Citizenship